Pancasila Sebagai Panduan Bersikap di Platform Media Sosial - Sislia Basaina Nubatonis; Yakobus Adi Saingo (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The modern era is closely related to technological developments, including social media. Therefore, social media must be utilized by every Indonesian citizen to disseminate the characteristic values ??of goodness, namely those based on the Pancasila ideology. The purpose of this research is to discuss Pancasila as a guide to behavior on social media platforms. This research uses a literature study method which is carried out by examining data originating from reference books, journals and scientific proceeding articles. The process of collecting data/information is carried out through written media, especially books and scientific journals related to the research focus which shows the results that Indonesian society and social media are closely related because there are many people who spend most of their time playing various social media platforms, therefore It is important for society to use social media wisely, manage information critically and build a positive online culture to support collective growth by using Pancasila as a guide for behavior on social media. Practicing Pancasila values ??can help create a positive online environment, avoid conflict and foster openness to the diversity of society. Upholding Pancasila values ??in social media can prevent negative attitudes such as the spread of hoaxes, fraud, hate speech, discrimination, content containing theory and pornography, brawls, provocations and so on.